Assessing Children's Dental Age with Panoramic Radiographs - Tal Ratson; Nurit Dagon; Netta Aderet; Eran Dolev; Amir Laviv; Moshe Davidovitch; Sigalit Blumer (MDPI AG, 2022)
(1) Background: The aim of the study was to assess the dental age of the subjects and compare it to their chronological age; to assess the dominant tooth for evaluation of dental age; and to investigate possible individual differences between the left and right side of the dental arch. (2) Methods: This study involved evaluating panoramic radiographs of patients aged 7-13 years. A separate assessment was performed for each tooth according to the degree of germ development. Each subject's dental age was estimated. (3) Results: The study involved evaluating 349 panoramic radiographs. No difference was found between stages of tooth development on the right side and left side. Correlation between the stages of tooth development and the chronological age was found to be highest in the second permanent molar teeth. The age can be predicted with the estimated age of tooth #37 and the gender of the patient. (4) Conclusions: The chronological age of children aged 7-13 may be estimated based on a modified seven-stage London Atlas of tooth development, where the most accurate landmark(s) of use are second molars.